VD_FINDINFO Jug / 2024 / 331 vom 12. Dezember 2023 - VD Tribunal cantonal (2023)
AMENDE, ERREUR SUR LES FAITSDROIT PÉNAL, LOI FÉDÉRALE SUR LES ÉTRANGERS ET L'INTÉGRATION | 106 al. 2 CP, 106 al. 3 CP, 13 CP, 117 al. 3 LEI